ALGORITHM OF JOINT OF SECTIONS OF THE REGULAR SMOOTH SURFACES - N E MISYURA; S S ZHILIN (Structural Mechanics of Engineering Constructions and Buildings, 2015)
This paper presents the method of joint of smooth analytic surfaces and an example of its application in architecture is given. This method is demonstrated on the mating surface of rev- olution formed by the generatrix curve in the form of a cubic parabola and the translation surface formed of the curve in the form of Guido Grandi. The same example shows torsion shaping for giving of a dynamic effect, and a matrix of torsion transformation is presented